2010
DOI: 10.1021/jp1047419
|View full text |Cite
|
Sign up to set email alerts
|

Control of Electrode Reactions in a Mixed-Potential-Type Gas Sensor Based on a BiCuVOx Solid Electrolyte

Abstract: Mixed-potential-type gas sensors are promising solid-state devices for the in-situ detection of ppm concentrations of air pollutants in the atmosphere. In this study, we designed electrode structures of mixed-potential-type sensors using a BiCuVOx (Bi 2 V 0.9 Cu 0.1 O 5.35 ) solid electrolyte to control the responses of electrodes to organic gases. Devices fitted with sensing and counter electrodes made of a composite of BiCuVOx and a perovskitetype oxide (La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3 ) were fabricated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…41 Control of the microstructure and thickness of the sensing electrode would lead to sensor responses to various gases, such as ethanol and toluene, as reported for high-temperature mixed-potential-type gas sensors. 42 The response to oxygen was also examined in the absence of hydrogen. The GO sensor responded to oxygen, as shown in Figure 5a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Control of the microstructure and thickness of the sensing electrode would lead to sensor responses to various gases, such as ethanol and toluene, as reported for high-temperature mixed-potential-type gas sensors. 42 The response to oxygen was also examined in the absence of hydrogen. The GO sensor responded to oxygen, as shown in Figure 5a.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the diffusion rate of hydrogen is probably high even in such a thick film electrode . Control of the microstructure and thickness of the sensing electrode would lead to sensor responses to various gases, such as ethanol and toluene, as reported for high-temperature mixed-potential-type gas sensors . The response to oxygen was also examined in the absence of hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kida et al the electrode material should be chosen carefully to enable gas sensing selectivity. 35 The change of resistance of the electrodes (alone) on exposure to the acetone using both Ru (Fig. S3c 3 ) and Ag (Fig.…”
Section: Gas Response Studymentioning
confidence: 99%
“…It was later found that a partial substitution of an aliovalent metal cation for vanadium (first was copper at 10 mol %) resulted in the stabilization of the γ-phase at room temperature, and the term BIMEVOX was coined to refer to this and all subsequent formulations, where ME represents one of the many possible substitutive metal cations, typically a transition metal [2]. Having an oxide ion conductivity that is higher than any other ceramic (e.g., yttria-stabilized cubic zirconia (Zr 1−x Y x O 2−x/2 "YSZ") at moderate temperatures, BIMEVOX compounds have generated interest over the years for their potential applications as solid oxide fuel cells, as oxygen separation pumps, as gas sensors [5][6][7][8][9], and very recently, as catalyst supports [10].…”
Section: Introductionmentioning
confidence: 99%